Pengaruh Bentuk Formulasi dan Waktu Aplikasi Kulit Buah Jengkol pada Pertumbuhan Padi Sawah Asal Bibit - Nurjanah, Uswatun; Yudono, Prapto; Suyono, A.T; Shieddiq, Dja’far (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2014)
Jengkol pod exocarp can be used as anorganic fertilizer for rice cultivation. A research aimed to determine an appropriate formulation and application time of jengkol pod exocarp on paddy rice seedling growth. Thisstudy consisted of 2 factors. The first factor was formulation, namely liquid, powder or granules. The second factor was time of application, namely at planting, 1 or 2 weeks after planting. These treatments were arrangedin a Completely Randomized Design with 3 replications. The results showed that the application of jengkol pod exocarp in the form of granule improved root growth, N, P, K uptake, photosynthesis rate, but not dry weight. Thetime application of jengkol pod exocarp two weeks after planting increased N and P uptake, transpiration rate, photosynthesis rate and root dry weight.